The Early Oxford Wyclif: Papalist or Nominalist? - Wilks, M. J. (Studies in church history, 1969)
From time to time it has been pointed out that Wyclif had a quite exceptional grasp of papal-hierocratic theory. Although its bitter opponent, his extensive knowledge of the refinements of the theory, his almost intuitive appreciation of its most fundamental principles, indicate a depth of penetration into hierocratic ideology which many supporters of papal supremacy must themselves have envied. His effectiveness as an anti-papal writer during the polemics of the 1370s and 1380s lay less in the novelty and originality of his own system of thought, and in the consistency with which he repeated himself, but rather in his superior ability to detect the weakest points in his adversaries’ chain of argument. He not only knew exactly where to thrust between the links, but, more important, how to aim for the pivots of the system, so that the whole hierocratic theory might be turned on its head.